2015
DOI: 10.1002/app.43027
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of poly(ethylene glycol) stabilized nano silver particles by a mechanochemical assisted ball mill process

Abstract: Nano silver particles with an average mean crystallite size of between 10 and 12 nm were synthesized from different molecular weights of poly(ethylene glycol) as a stabilizing agents, through solid state oxidation of silver nitrate using a higher energy planetary ball mill. Ultraviolet-Visible spectra were used to confirm the synthesis of nano silver particles. The surface plasmon resonance bands were observed around 410 nm. Fourier transformed infrared spectrum, X-ray diffraction, and transmission electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
55
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(65 citation statements)
references
References 47 publications
(67 reference statements)
10
55
0
Order By: Relevance
“…For G 1 ICD, the peak at -C=O stretching frequency of ester group was 1730 cm −1 and in G 2 ICD peak contains at 1722 cm −1 respectively. The new distinguished peaks appeared at 548 cm −1 and 600 cm −1 for G 1 ICD and G 2 ICD respectively, which confirmed the successful incorporation of AuNPs in hydrogels [40]. It also evidenced from band appeared at 1456 cm −1 attributed to -COO − stretching for G 1 ICD and 1487 cm −1 for G 2 ICD with the addition of shifting some of the important peaks of -OH, -CH 2, and -NH towards the lower region.…”
Section: Fourier Transform Spectroscopy (Ft-ir)supporting
confidence: 53%
“…For G 1 ICD, the peak at -C=O stretching frequency of ester group was 1730 cm −1 and in G 2 ICD peak contains at 1722 cm −1 respectively. The new distinguished peaks appeared at 548 cm −1 and 600 cm −1 for G 1 ICD and G 2 ICD respectively, which confirmed the successful incorporation of AuNPs in hydrogels [40]. It also evidenced from band appeared at 1456 cm −1 attributed to -COO − stretching for G 1 ICD and 1487 cm −1 for G 2 ICD with the addition of shifting some of the important peaks of -OH, -CH 2, and -NH towards the lower region.…”
Section: Fourier Transform Spectroscopy (Ft-ir)supporting
confidence: 53%
“…Thermo gravimetric analysis (TGA) was elucidating about the weight loss of the PEG polymer electrolyte. Figure 9 shows the PEG polymer electrolyte weight loss at 420°C the scan range fixed between the 50°C-500°C [38]. The TGA graph indicates that the DPT well interact with PEG and maintains the thermal stability and confirms that the synthesized organic compound doped polymer electrolyte decomposed above 420°C.…”
Section: Dsc and Tga Studiesmentioning
confidence: 83%
“…FTIR spectra of PEG-6000 presented the characteristic peaks at 1109 and 2870 cm −1 that was related to stretching of the ether group (C-O-C) and the peaks towards higher temperature. In another study performed by Jayaramudu et al [51] improvement in thermal stability of PEG-6000 was reported when complexed with silver. ermal analysis of prepared formulation presented a better thermal stability as compared to individual ingredients that proposed a condensed structure for prepared nanogels.…”
Section: 8mentioning
confidence: 88%